2020
DOI: 10.3389/fonc.2020.00653
|View full text |Cite
|
Sign up to set email alerts
|

Signet-Ring Cell Carcinoma as an Independent Prognostic Factor for Patients With Urinary Bladder Cancer: A Population-Based Study

Abstract: Background: Primary signet-ring cell carcinoma (SRCC) is a rare variation of adenocarcinoma. Although SRCC of the urinary bladder is highly malignant, it is often neglected due to its rarity. Materials and Methods: We used the national Surveillance, Epidemiology, and End Results (SEER) database (2004-2016) to compare SRCC with urothelial carcinoma (UC) and investigated the prognostic values of the clinicopathological characteristics and survival outcomes in SRCC of the urinary bladder. Multivariable Cox propor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
21
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(22 citation statements)
references
References 22 publications
1
21
0
Order By: Relevance
“…Nomograms are currently one of the most widely used prediction tools, owing to their ability to combine clinical characteristics in generating individual probabilities of clinical events, which could provide clinical decision-making and personalized medical therapy; pure UC and concluded that SRCC was an independent predictor of inferior CSS in contrast to pure UC (16). Similarly, Jin et al reported that compared with pure UC, SRCC was significantly associated with a higher risk of overall and cancer-specific mortality (8). The highly aggressive behaviors and uncertain efficacy of multimodality treatments may result in poor SRCC prognosis.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Nomograms are currently one of the most widely used prediction tools, owing to their ability to combine clinical characteristics in generating individual probabilities of clinical events, which could provide clinical decision-making and personalized medical therapy; pure UC and concluded that SRCC was an independent predictor of inferior CSS in contrast to pure UC (16). Similarly, Jin et al reported that compared with pure UC, SRCC was significantly associated with a higher risk of overall and cancer-specific mortality (8). The highly aggressive behaviors and uncertain efficacy of multimodality treatments may result in poor SRCC prognosis.…”
Section: Discussionmentioning
confidence: 99%
“…Among the BCa types, the major histological type is urothelial carcinoma (UC), while primary signet ring cell carcinoma (SRCC) is rare, accounting for approximately <1% of cases (3,4). Compared with UC, SRCC tends to be associated with worse oncological outcomes, but the prevalent characteristics, treatment options, and prognosis are not comprehensively characterized because of their low occurrence rate (5)(6)(7)(8).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Otherwise, the clinical context of the patient and a basic immunohistochemical panel, for example, CK7/20, GATA-3, CDX-2, and p63, should resolve the dilemma. The analysis of the national Surveillance, Epidemiology, and End Results (SEER) database of 318 such cases confirms the worse prognosis of this histologic variant compared with conventional UC [ 45 ].…”
Section: Cytological Changesmentioning
confidence: 99%
“… 6 In addition, the extensive sample size and statistical validity of the SEER database contribute to the superior value of SEER‐based studies. 7 Similar to those rare diseases, no standardized proposal is available for PACC. Our present knowledge of PACC is mainly derived from case reports or review.…”
Section: Introductionmentioning
confidence: 99%